PENGEMBANGAN USAHA OLAHAN DADIH PADA RUMAH DADIH YOGHMI DI KOTA PADANG PANJANG - Helmizar Helmizar; Virtuous Setyaka; Susmiati Susmiati (Jurnal Hilirisasi IPTEKS, 2022)
Rumah Dadih Yoghmi produces traditional Minangkabau food namely dadih with a concept marketing mix. The basic problem experienced by rumah dadih yoghmi are in production side, which is produce perishable food and also on unsystematic marketing stategies. This program aims to increase marketing, production, and income at rumah dadih yoghmi. The method of services activities carried out by provifing counseling and meeting with partners and product user communities. Partners participate in outreach activities to support innovations that will be made and evaluate activities using market tests. The solution that offered to solve the problems are: 1) to make inovations for long-lasting dadih product who stored at room temperatured, 2) to broad marketing strategy with wholesale or supermarket food traders with a deposit system, 3) to make attractive product packaging by including product expiration. In the first year conducting market research on the causes of low purchasing prices for processed dadih, making production design, testing and training on new product formulations that have a long shelf life. The next year’s implementation stage is to innovate new products in accordance with the agreement with partners and evaluate the training that has been provided. From the result of the activity, various food product from dadih which can be used by the community health centre as additional food for pregnant women and toddlers in Padang Panjang district.